Comparative Analysis of Qiraat in Surah At-Tin and Al-'Alaq: A Case Study of Qiraat Hafs and Warsy - Ustazdah, Nimah; Nugroho, Kharis (Universitas Muhammadiyah Surakarta, 2024)
This paper discusses the comparison of the reading of the Qur'an which is quite significant between the narration of Hafs and the narration of Warsy in Surah At-Tin and Al-'Alaq and is presented in the form of a comparison between the two narrations according to thariq as-Syathibiyyah accompanied by the biography of each qiraat imam. This study resulted in different readings: mim jama', mad jaiz munfasil, mad wajib muttasil, mad badal, imalah, naql, and tarqiq ra'. The author found 6 differences in readings in Surah At-Tin, and 20 differences in readings in Surah Al-'Alaq which Most of the readings differ in naql and imalah sughra/taqlil.